The Impact of Non-Audit Services on Earning Response Coefficient - Vahdani, Mohammad (2021)
The present study aims to investigate the impact of non-audit services on earnings response coefficient. It is a library and analytical-scientific research and is based on panel data analysis. In this study, the financial data of 74 companies accepted in Tehran Stock Exchange during the period 2011-2016 have been reviewed.The results demonstrate that non-audit services have a significant negative relationship with earnings response coefficient.Although non-audit services will have benefits such as increased financial statements understandability, auditors’ knowledge-sharing, better relationships between managers and auditors and reduced agency costs, this type of services threatens auditor independence and subsequently, earnings quality will be affected. Thus,the findings of the present study confirm the view thatby providing non-audit services, auditor independence is affected, resulting in a negative reaction to earnings.